A tale of airline competition: When full-service carriers undercut low-cost carriers fares. (May 2021) - Avogadro, Nicolò; Malighetti, Paolo; Redondi, Renato; Salanti, Andrea
Abstract: The pricing of low-cost carriers (LCCs) compared with traditional airlines has been extensively investigated since their inception in the air transport market. Abundant empirical evidence attests that, on average, LCCs' fares (per km) are lower than those usually offered by full-service carriers (FSCs). Such literature, however, paid virtually no attention to the conditions under which LCCs lose their convenience compared to traditional airlines. The purpose of this study is to investigate the occurrence of LCCs sometimes offering higher fares than FSCs on competing flights. By using a dataset expressly collected for this purpose, we are able to quantify its frequency and suggest some possible explanations. These findings concur to cast some questions on the widely held preconception of vertical differentiation between LCCs' and FSCs' offered services. Further research will be needed in order to understand the relative weight of the suggested factors. Highlights: The article analyses the cases in which LCCs offer higher fares than FSCs on competing flights. The phenomenon is more likely when approaching the date of the flight. "Price reversal" is related to passengers' search habits and airlines' reputations. The phenomenon is more frequent on routes connecting multi-airport cities. We identify the typical price interactions between LCCs and FSCs leading to the phenomenon.